IMPLEMENTASI PROGRAM BPJS KETENAGAKERJAAN BAGI PERANGKAT DESA DI KABUPATEN SUMEDANG - Giri Sudirman Mita Jaya (JRPA - Journal of Regional Public Administration, 2026)
This This study aims to comprehensively analyze the implementation of the BPJS Ketenagakerjaan program for village officials in Sumedang Regency, focusing on program implementation, the obstacles encountered, and the efforts made to overcome these obstacles. This objective is expected to provide an empirical and systematic overview of the effectiveness of the employment social security policy at the village level as well as strategic recommendations for strengthening its implementation. The method used in this study is a qualitative approach, which aims to gain an in-depth understanding of the implementation of the BPJS Ketenagakerjaan program and how to overcome these obstacles. Through in-depth interviews, observation, and document analysis, this study identified various factors influencing the implementation of the BPJS Ketenagakerjaan program, efforts made to address these challenges, and efforts to overcome obstacles to the implementation of the BPJS Ketenagakerjaan program for village officials in Sumedang Regency. Based on the research results, it can be concluded that the implementation of the BPJS Ketenagakerjaan program for village officials in Sumedang Regency has not been running optimally. Several major obstacles hinder its effectiveness, such as the high rate of late payment of contributions (late payment of contributions), poor response and service from BPJS Ketenagakerjaan regarding administrative issues, and minimal participation of village officials in outreach and training activities. These factors directly impact the level of compliance and awareness of village officials regarding participation in the social security program, ultimately disrupting the program's sustainability and goal of providing comprehensive social protection. Therefore, improvements in the service system, increased communication between parties, and strengthened commitment from both village officials and BPJS Ketenagakerjaan to support the program's implementation are needed.